Economia criativa e resistência: o artesanato indígena no Estado do Rio de Janeiro - Diego Santos Vieira de Jesus (Ciências Sociais Unisinos)
The purpose of this article is to examine the socioeconomic, cultural and political roles of craft to the indigenous population living on authorized indigenous land in Rio de Janeiro and its capital. The central argument suggests that craft has not only the role of income and employment generation in the context of the development of creative economy in the state, but also the resistance to marginalization of indigenous people in public policies and state and federal laws, as well as their invisibility in craftsmen’s social organizations. Craft can lead to greater autonomy and development of indigenous communities by linking aesthetic, symbolic and social elements of local crafts to the improvement of the political and socioeconomic living conditions of communities in the context of the stimulus to creative sectors in areas of the state of Rio de Janeiro. At the same time, craft offers greater visibility to cultural production of marginalized social groups such as indigenous people and brings potentially transformative discussions about their conditions and position in public policies and laws aimed at the craft itself, as well as the craftsmen’s social organizations.